Genomic epidemiology of antimicrobial resistance determinants in Chinese swine farm Escherichia coli isolates - Hu, Zizhe; Huang, Yee; Cui, Xuemei; Shi, Tuanyuan; Ji, Quanan; Wang, Xiangru; Bao, Guolian; Liu, Yan (Frontiers in Microbiology, 2025)
IntroductionThe extensive use of antimicrobials in pig farming has led to a significant emergence of antimicrobial resistance (AMR) among microorganisms. Given China’s prominent position as the leading global swine producer, AMR in pig farming has become a focal point of debates. However, limited research has comprehensively assessed the overall status of AMR in Chinese pig farms.MethodsSamples were collected from 31 provinces in China. E. coli was identified and isolated using McConkey’s selective medium and confirmed through PCR amplification. The MIC value was determined by BD Phoenix™ M50 Automated Identification and Susceptibility device. E. coli J53 (sodium azide-resistant) was used as the recipient in conjugation transfer experiment. The phenotypic and genotypic characteristics of the isolates were comprehensively analyzed using whole-genome sequencing.Results227 slurry samples were collected from 52 pig farms located across 31 provinces in seven geographical regions of China. 142 non-duplicate strains of E. coli were isolated, and their resistance phenotypes to 28 antimicrobials were systematically evaluated. ST10 and ST641 isolates were widespread sequence types with numerous antimicrobial resistance genes (ARGs) and virulence factor genes, including blaNDM-1, mcr-1.1, and blaOXA-10, among others. Multiple ARGs were co-located on a single plasmid, and an analysis of the genetic context revealed insertion sequences adjacent to ARGs containing various mobile genetic elements. Conjugation experiments provided additional evidence for the horizontal dissemination of these ARGs.DiscussionThe release of E. coli into the environment via farm slurry comprises a significant emerging contaminant and a potential hazard to public health. Consequently, there is an urgent need to establish universally recognized farm effluent standards for monitoring the dissemination of resistant bacteria and ARGs in China’s pig farms.